Plato on the Traditional Definition of Knowledge - Pereira da Silva, Jose Lourenço (Revista Archai, 2018)
In Plato’s dialogues, Socrates often contrasts opinion (doxa) with knowledge (episteme), as a fallible form of cognition against an infallible one. He seems to suggest that by attaching to a true opinion a ‘calculation of cause’ or some sort of account, we can convert it into knowledge. Many scholars and epistemologists have taken this suggestion as evidence that the traditional definition of knowledge as justified true belief traces back to Plato. In this paper, I claim that it is inaccurate to suppose that Plato foresaw the tripartite analysis of knowledge of the Contemporary Epistemology. Focusing on the theory of recollection and the distinction between true opinion and knowledge in the Meno, I intent to show that the two-world metaphysics implies the treatment of opinion and knowledge as cognitions which are essentially different and mutually irreducible. Also, since Socrates was mainly concerned with the notion of knowledge as knowing what (is) which requires an apprehension of essences or Forms, he did not pay particular attention to the knowing that. As a result, Socrates did not argue to establish the conditions of justification to be given propositionally in order for a belief becomes knowledge.